Further evidence for asymptotic safety of quantum gravity - Falls, Kevin; Litim, D.; Nikolakopoulos, K.; Rahmede, C. (Physical review, 2016)
The asymptotic safety conjecture is examined for quantum gravity in four dimensions. Using the renormalization group, we find evidence for an interacting UV fixed point for polynomial actions up to the 34th power in the Ricci scalar. The extrapolation to infinite polynomial order is given, and the self-consistency of the fixed point is established using a bootstrap test. All details of our analysis are provided. We also clarify further aspects such as stability, convergence, the role of boundary conditions, and a partial degeneracy of eigenvalues. Within this setting we find strong support for the conjecture.